Strategi Akomodasi Komunikasi dalam Proses Pembelajaran Bahasa Indonesia - Reza Amarta Prayoga; Dian Palupi (Badan Pengembangan dan Pembinaan Bahasa, 2020)
The ability of teachers and students in learning activities is greatly influenced by the communication between the two. To establish interactive communication between the two, to achieve learning objectives, language adjustment, or adaptation (accommodation) is carried out so that mutual learning occurs. There are strategies carried out by teacher-students, both consciously and unconsciously, to adapt (accommodation) language in learning activities. Writing this article aims to (a) describe the dominance of the use of communication accommodation strategies in classroom learning and (b) describe the reasons or factors that influence the use of communication accommodation strategies between teachers and students in classroom learning. The data sources of this research are teachers and students in Indonesian language learning activities in classes in three high schools in Jakarta. The research data is verbal and nonverbal speech in Indonesian language learning activities. This research method uses descriptive qualitative which relies on data in the form of interviews, observation notes, and audiovisual recordings of Indonesian language learning activities in three high schools in Jakarta. The results showed that three strategies, namely the management of discourse, emotional expression, and interpretability dominate the use of communication accommodation strategies by teachers and students. Simplifying messages and building self-confidence are the reasons or factors for the occurrence of communication accommodation strategies that are built in the language interactions of teachers and students in the classroom. AbstrakKemampuan guru dan siswa dalam kegiatan pembelajaran sangat dipengaruhi oleh komunikasi antarkeduanya. Untuk menjalin komunikasi yang interaktif antarkeduanya dalam upaya mencapai tujuan pembelajaran, penyesuaian atau adaptasi (akomodasi) bahasa dilakukan. Tujuannya ialah terjadinya pembelajaran yang timbal balik. Ada strategi-strategi yang dilakukan oleh guru-siswa, baik secara sadar maupun tidak sadar, untuk melakukan adaptasi (akomodasi) bahasa dalam kegiatan pembelajaran. Penulisan artikel ini bertujuan untuk (a) mendeksripsikan dominasi penggunaan strategi akomodasi komunikasi dalam pembelajaran di kelas dan (b) mendeskripsikan alasan atau faktor yang memengaruhi penggunaan strategi akomodasi komunikasi antara guru dan siswa dalam pembelajaran di kelas. Sumber data penelitian ini berupa guru dan siswa dalam kegiatan pembelajaran bahasa Indonesia di kelas pada tiga SMA di Jakarta. Data penelitiannya adalah tuturan verbal dan nonverbal dalam dalam kegiatan pembelajaran bahasa Indonesia. Penelitian ini menggunakan metode kualitatif deskriptif yang mengandalkan data berupa hasil wawancara, catatan observasi, dan rekaman audiovisual kegiatan pembelajaran bahasa Indonesia di tiga SMA di Jakarta. Hasil penelitian menunjukkan bahwa tiga strategi, yaitu pengelolaan wacana, emotional ekspresi, dan interpretabilitas mendominasi penggunaan strategi akomodasi komunikasi yang dilakukan guru dan siswa. Penyederhanaan pesan dan pembangunan kepercayaan diri menjadi alasan atau faktor terjadinya strategi akomodasi komunikasi yang dibangun dalam interaksi bahasa guru dan siswa di kelas.